2020
DOI: 10.2196/21366
|View full text |Cite|
|
Sign up to set email alerts
|

Work-Related and Personal Factors Associated With Mental Well-Being During the COVID-19 Response: Survey of Health Care and Other Workers

Abstract: Background The response to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has created an unprecedented disruption in work conditions. This study describes the mental health and well-being of workers both with and without clinical exposure to patients with coronavirus disease (COVID-19). Objective The aim of this study is to measure the prevalence of stress, anxiety, depression, work exhaustion, burnout, and decreased well-bein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
258
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(288 citation statements)
references
References 21 publications
19
258
2
9
Order By: Relevance
“…As shown in Table 1, the majority of studies were from China (n = 43, 49%), followed by the United States (n = 7), Italy (n = 5), Singapore (n = 3), Turkey (n = 4), Iran (n = 3), Pakistan (n = 3), India (n = 2), Poland (n = 2), Saudi Arabia (n = 2), Spain (n = 2), Colombia (n = 1), Ecuador Many studies found that women experience worse mental health outcomes on multiple instruments as compared to men. 6,8,14,17,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Table 1, the majority of studies were from China (n = 43, 49%), followed by the United States (n = 7), Italy (n = 5), Singapore (n = 3), Turkey (n = 4), Iran (n = 3), Pakistan (n = 3), India (n = 2), Poland (n = 2), Saudi Arabia (n = 2), Spain (n = 2), Colombia (n = 1), Ecuador Many studies found that women experience worse mental health outcomes on multiple instruments as compared to men. 6,8,14,17,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45…”
Section: Resultsmentioning
confidence: 99%
“…13,21,22,27,32,37,49,50,51 These adverse outcomes were also seen in HCWs with friends or family with COVID-19 infection 22,32,33,34,49 and in HCWs with colleagues who were hospitalized or died of COVID-19. 39 Further, working in COVID-19 designated hospitals compared to nondesignated hospitals 25,49,52 and working in COVID-19 specific isolation wards 13,22,40,45 were associated with poorer mental health outcomes. However, smaller single-institution studies in Romania 53 and in Guangzhou, China, 54 where there were fewer COVID-19 cases, did not find differences in mental health outcomes between HCWs working in dedicated versus nondedicated wards.…”
Section: Covid Exposure and Infectionmentioning
confidence: 98%
See 2 more Smart Citations
“…[22] Some data on U.S. HCWs have begun to emerge, with data from a survey of U.S. university employees in April 2020 demonstrating that those working in a clinical capacity had higher anxiety and lower emotional wellbeing compared to nonclinical workers. [23] A survey of residents and clinical fellows at the same university's training program, who were also surveyed in April 2020, found that trainees exposed to COVID-19 patients reported significantly higher stress, burnout, and anxiety than non-exposed trainees. [24] Both groups reported levels of depression consistent with prior studies of resident physicians, as well as similarly low professional fulfillment from their current clinical activities.…”
Section: Mental Health Concerns Of Front-line Hcws During the Pandemicmentioning
confidence: 99%